2017
DOI: 10.1371/journal.pone.0177698
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone reminders and peer counseling improve adherence and treatment outcomes of patients on ART in Malaysia: A randomized clinical trial

Abstract: BackgroundAdherence to treatment remains the cornerstone of long term viral suppression and successful treatment outcomes among patients receiving Antiretroviral Therapy (ART).Objective(s)Evaluate the effectiveness of mobile phone reminders and peer counseling in improving adherence and treatment outcomes among HIV positive patients on ART in Malaysia.MethodsA single-blind, parallel group RCT conducted in Hospital Sungai Buloh, Malaysia in which 242 adult Malaysian patients were randomized to intervention or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 24 publications
5
88
0
6
Order By: Relevance
“…In the last 10 years growing evidence showed that mobile phone reminders (text messages and phone calls) can be used to improve attendance to healthcare appointments, increase access to health care, improve adherence to treatment, follow-up and rehabilitation and improves the efficiency of health service delivery [21][22][23]. Randomized trials indicated mobile phone reminder improves appointment compliance [20,23,24], adherence to ART and Tb medications [25,26]. In addition, it facilitates provision of health education, counseling [27,28] and behavioral change interventions [17,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years growing evidence showed that mobile phone reminders (text messages and phone calls) can be used to improve attendance to healthcare appointments, increase access to health care, improve adherence to treatment, follow-up and rehabilitation and improves the efficiency of health service delivery [21][22][23]. Randomized trials indicated mobile phone reminder improves appointment compliance [20,23,24], adherence to ART and Tb medications [25,26]. In addition, it facilitates provision of health education, counseling [27,28] and behavioral change interventions [17,29].…”
Section: Introductionmentioning
confidence: 99%
“…Un método innovador y económico es el uso de las tecnologías de la información y comunicación (TIC), especialmente el envío de mensajes de texto (SMS) a los pacientes. Algunos ensayos aleatorizados controlados han demostrado que esta intervención es beneficiosa para los pacientes con VIH (9,10,11) . Sin embargo, hay otros estudios donde la intervención no mejoró la adherencia de los pacientes (12,13) .…”
Section: Mensajes Clave Introducciónunclassified
“…It is also inherently evident that most of the studies reviewed in this paper were undertaken over shorter periods of time (between 2 years and 4 days). Whereas this is a limitation beyond this paper, it is a calling for longitudinal studies and long term programmatic efforts that would provide more detailed evidence [40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%